1994
DOI: 10.1017/s0952523800001747
|View full text |Cite
|
Sign up to set email alerts
|

The retinal targets of centrifugal neurons and the retinal neurons projecting to the accessory optic system

Abstract: In birds, neurons of the isthmo-optic nucleus (ION), as well as “ectopic” neurons, send axons to the retina, where they synapse on cells in the inner nuclear layer (INL). Previous work has shown that centrifugal axons can be divided into two anatomically distinct types depending on their mode of termination: either “convergent” or “divergent” (Ramon y Cajal, 1889; Maturana & Frenk, 1965). We show that cytochrome-oxidase histochemistry specifically labels “convergent” centrifugal axons and target neurons wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 27 publications
6
39
0
Order By: Relevance
“…In the absence of definitive evidence, we assume that the ION neurons are excitatory, a view that is supported by evidence that at least some of them contain choline acetyltransferase (Bagnoli et al, 1992) and that their target cells receiving pericellular nests express excitatory nicotinic receptors (Nickla et al, 1994). Moreover, the only GABAergic neurons in the ION are a tiny population of interneurons (Miceli et al, 1995).…”
Section: A Proposed Circuit For Attentional Switchingmentioning
confidence: 94%
“…In the absence of definitive evidence, we assume that the ION neurons are excitatory, a view that is supported by evidence that at least some of them contain choline acetyltransferase (Bagnoli et al, 1992) and that their target cells receiving pericellular nests express excitatory nicotinic receptors (Nickla et al, 1994). Moreover, the only GABAergic neurons in the ION are a tiny population of interneurons (Miceli et al, 1995).…”
Section: A Proposed Circuit For Attentional Switchingmentioning
confidence: 94%
“…The authors supposed that the centrifugal axons act by increasing the gain on the accessory optic system, thereby enhancing retinal stabilization of gaze with improved accuracy of pecking of small objects. Nickla et al [48] showed that cytochrome-oxidase histochemistry in chicken retina specifically labels convergent centrifugal axons and target neurons which appear to be amacrine cells, as well as three types of ganglion cells: two types found in the inner nuclear layer (INL) (displaced ganglion cells) and one in the ganglion cell layer. Labeled target amacrine cells have distinct darkly labeled nests of boutons enveloping the somas.…”
Section: Termination Of Retinopetal Fibersmentioning
confidence: 99%
“…Histamine is expected to be released from retinopetal axons during the day in diurnal animals and during the night in nocturnal animals. While GABA [57,58], glutamate, NO [59] and acetylcholine [48] are involved in the function of the centrifugal visual system in sub-mammalian species, these transmitters are not described in mammals. In our material the majority of the neurons giving rise to the centrifugal visual fibers in the rat were present in the DG [25].…”
Section: Termination Of Retinopetal Fibersmentioning
confidence: 99%
“…Nickla and co-workers (7) demonstrated immunoreactivity against the alpha-7 subunit of the nicotinic acetylcholine receptor (nAChR) in centrifugal fibers and in ION neurons in chick species (7). In addition, high levels of choline acetyltransferase (ChAT) activity have been reported in homogenates of chick and pigeon mesencephalon (8).…”
Section: Introductionmentioning
confidence: 99%